2019
DOI: 10.1021/acs.biomac.8b01704
|View full text |Cite
|
Sign up to set email alerts
|

Glycopolycation–DNA Polyplex Formulation N/P Ratio Affects Stability, Hemocompatibility, and in Vivo Biodistribution

Abstract: Genome editing therapies hold great promise for the cure of monogenic and other diseases; however, the application of nonviral gene delivery methods is limited by both a lack of fundamental knowledge of interactions of the gene-carrier in complex animals and biocompatibility. Herein, we characterize nonviral gene delivery vehicle formulations that are based on diblock polycations containing a hydrophilic and neutral glucose block chain extended with cationic secondary amines of three lengths, poly(methacrylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…115 Along with avoiding hemolysis or altering blood coagulation, nonviral gene delivery vehicles must not activate the complement system to be considered hemocompatible. 116 Complement activation has been observed for liposomes, naked phosphorothioate oligonucleotides, and polyplexes, as well. 112,116,117 While naked polycations such as PLL, poly(amidoamine) (PAMAM) dendrimers, and PEI can all strongly activate the complement system, this activation is greatly diminished by charge neutralization with nucleic acid cargo.…”
Section: Extracellular Barriersmentioning
confidence: 98%
See 1 more Smart Citation
“…115 Along with avoiding hemolysis or altering blood coagulation, nonviral gene delivery vehicles must not activate the complement system to be considered hemocompatible. 116 Complement activation has been observed for liposomes, naked phosphorothioate oligonucleotides, and polyplexes, as well. 112,116,117 While naked polycations such as PLL, poly(amidoamine) (PAMAM) dendrimers, and PEI can all strongly activate the complement system, this activation is greatly diminished by charge neutralization with nucleic acid cargo.…”
Section: Extracellular Barriersmentioning
confidence: 98%
“…116 Complement activation has been observed for liposomes, naked phosphorothioate oligonucleotides, and polyplexes, as well. 112,116,117 While naked polycations such as PLL, poly(amidoamine) (PAMAM) dendrimers, and PEI can all strongly activate the complement system, this activation is greatly diminished by charge neutralization with nucleic acid cargo. 117−119 In addition, it was found that complement activation was strongly dependent on polymer chain length, with cationic oligomers showing a weak activation.…”
Section: Extracellular Barriersmentioning
confidence: 99%
“…Recent work by our group and others in the field has begun to address this problem by developing structure-property, and in some cases structure-property-function relationships for PCMs formed from nucleic acids and various cationic-neutral polymers 7,[25][26][27] . Two consistent themes that have emerged from these studies are the importance of developing well-controlled, repeatable protocols for PCM assembly and the benefit of using multiple techniques to characterize the resulting nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, naked plasmid DNA (pDNA) encoding human hepatocyte growth factor (HGF) gene was first approved for clinical gene therapy in Japan 1–3 . Compared with other candidates, pDNA can synthesize various copies of emerging nucleic acid agents, such as short interfering RNA, messenger RNA, and non‐coding RNA, as well as proteins 4–9 . However, pDNA needs to overcome many barriers for clinical application of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Compared with other candidates, pDNA can synthesize various copies of emerging nucleic acid agents, such as short interfering RNA, messenger RNA, and non-coding RNA, as well as proteins. [4][5][6][7][8][9] However, pDNA needs to overcome many barriers for clinical application of gene therapy. In Asayama's recent review, 10 various molecular design of polymer-based carriers as supramolecular systems for pDNA delivery in vitro and in vivo has been reported, [11][12][13][14] including ours.…”
Section: Introductionmentioning
confidence: 99%